2011
DOI: 10.1186/1475-2875-10-52
|View full text |Cite
|
Sign up to set email alerts
|

Atorvastatin prevents Plasmodium falciparum cytoadherence and endothelial damage

Abstract: BackgroundThe adhesion of Plasmodium falciparum parasitized red blood cell (PRBC) to human endothelial cells (EC) induces inflammatory processes, coagulation cascades, oxidative stress and apoptosis. These pathological processes are suspected to be responsible for the blood-brain-barrier and other organs' endothelial dysfunctions observed in fatal cases of malaria. Atorvastatin, a drug that belongs to the lowering cholesterol molecule family of statins, has been shown to ameliorate endothelial functions and is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0
3

Year Published

2012
2012
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(36 citation statements)
references
References 50 publications
1
32
0
3
Order By: Relevance
“…It is possible that the inhibition of cholesterol synthesis by statins results in reduced parasite invasion or reduced parasite growth. Interestingly, a recent study has shown that atorvastatin treatment of endothelial cells reduced cytoadherence of Plasmodium falciparum [37].…”
Section: Discussionmentioning
confidence: 99%
“…It is possible that the inhibition of cholesterol synthesis by statins results in reduced parasite invasion or reduced parasite growth. Interestingly, a recent study has shown that atorvastatin treatment of endothelial cells reduced cytoadherence of Plasmodium falciparum [37].…”
Section: Discussionmentioning
confidence: 99%
“…Statins also directly decrease the expression of endothelial adhesion molecules, such as ICAM-1, VCAM-1 and E-selectin [21,22]; moreover, they can prevent P. falciparum cytoadherence and endothelial damage [23];…”
Section: Introductionmentioning
confidence: 99%
“…This modulation may prevent the cytoadherence at concentrations higher than 0.5 μM of AVA and endothelial damage related to CM or it may inhibit diapedesis, due to its pleiotropic effects [29-31]. A dose of 0.5 μM is relevant with plasma concentrations expected in clinical observations for patients taking 80 mg of AVA daily [15].…”
Section: Discussionmentioning
confidence: 99%